The Convergence of Sufism and Sharia: The Spiritual Basis of Family Resilience in Shiddiqiyah Congregation in Jombang, Indonesia - Maliki Abitolkha, Amir; Thahir, A. Halil; Muzakki, Akh; Dodi, Limas (El-Usrah: Jurnal Hukum Keluarga, 2025)
Sufi teachings play a strategic role in strengthening family resilience, particularly among the Shiddiqiyah Order community in Jombang. Sufi doctrine forms the basis for fulfilling social responsibilities as an expression of obedience to God. Sufi teachings erode worldly desires, lust and hedonism within the family, which pose a serious threat to resilience. This study aims to strengthen family functions through a Sufi approach, which in the process creates strong cohesion between Sufism and Sharia. Family resilience is created and shaped by the convergence of spirituality contained in the teachings of the order. Members of the order are able to adapt to mental, social and even economic crises through psychological and spiritual resilience. This concept is the answer to family breakdown and fragmentation caused by authoritarianism and hedonism. How is the concept of family resilience built by Sufi followers? How can Sufi teachings strengthen family resilience? This is a qualitative study, with primary data obtained from interviews and documentation. The results of the study show that the teachings of the Shiddiqiyah Order teach a balance between the Sufi and Sharia dimensions. The rituals of dzikir jahr and the heart are directed at strengthening the relationship with God, while still making worldly functions a manifestation of faith. From zikr, heart rituals and manifestations of faith can give meaning to family relationships, strengthen emotions and create openness in communication, healthy emotional expression through the concept of muhasabah as a spiritual instrument. It is this process that enables the families of the Shiddiqiyah Order to survive and harmoniously establish symbiotic relationships within the family.